Transformation of Madrasah Management in the Digital Era: Leadership, Implementation, and Educational Innovation - Yusuf, Munir (Journal of Indonesian Islamic Studies, 2024)
The rapid expansion of digital technologies has redefined educational management, yet its implementation in madrasahs remains uneven and context-dependent. While prior studies predominantly frame digital transformation as a technological or individual competency issue, limited attention has been given to its relational and organizational dynamics. Addressing this gap, this study examines how leadership, implementation processes, and educational innovation interact to shape digital transformation in madrasah contexts. Adopting a qualitative multi-site case study design, data were collected from three madrasahs in Palopo City through in-depth interviews, observations, and document analysis, and analyzed using thematic analysis. The findings reveal that digital transformation unfolds as a gradual and socially embedded process, driven by adaptive leadership and sustained through teacher collaboration, yet constrained by infrastructural limitations that produce uneven implementation. While digital innovation enhances administrative efficiency and student engagement, its impact remains contextually variable. This study advances the literature by reconceptualizing digital transformation in education as a relational and context-sensitive process rather than a purely technological transition, highlighting the critical role of leadership–teacher interaction and adaptive implementation strategies in shaping sustainable digitalization. The findings offer important implications for policy and practice, particularly in designing context-responsive digital transformation strategies in resource-constrained educational settings.